Too Generous and Committed: Hullabaloos over Nigerian Foreign Policy Objectives - Dauda, Muritala; Bin AHMAD, Mohammad Zaki; Keling, Mohammad Faisol (Journal of Techno-Social, 2021)
AbstractNigeria’s afrocentric foreign policy has in no small measure benefited African continent. This has assisted Nigeria tremendously to have played a leading role towards ensuring peace, stability, cooperation and development in the African continent. The study examines the hullabaloos surrounding the too generous and committed nature of Nigerian foreign policy which has canvassed for varieties of opinions on the need for the country to adjust her foreign policy objectives. The study indicates that if there is need for Nigeria to adjust her foreign policy objectives towards Africa, it should be more favourable and not the other way round due to numerous unforeseen benefits. The study adopts role theory to describe the position and responsibility shouldered by Nigeria in Africa. As against the position opined by antagonists on the amendment of Nigerian foreign policy’s objectives, the theory explains that some benefits are either tangible or intangible forms. This study is qualitative that adopts both primary and secondary sources of data. Twelve (12) respondents were interviewed from various Nigerian government parastatals and higher institutions of learning. Data gotten from the interview was analysed thematically with the aid of Nvivo.